A Rare Case of Bilateral Pulmonary Sequestration Managed with Embolization and Surgical Resection in a Patient - Seok, June Pill (Korean Society for Thoracic and Cardiovascular Surgery, 2013)
In this article, we report a rare case of a 22-year-old male with bilateral pulmonary sequestration, treated with embolization and surgical resection. The initial plan involved staged bilateral lobectomy for both lungs and prophylactic embolization of feeding vessels for preventing unexpected hemorrhage during operation. Symptomatic right lower lobe was resected with video-assisted thoracic surgery after embolization, and the patient refused surgery of left lower lobe upon symptomatic relief. The two-year follow-up examination revealed that the patient was healthy and had no relevant discomfort.